Homogenizing microwave pyrolysis of oily sludge using nano-Fe3O4 volatile gas product analysis - Yan, Jing (Environmental technology, 2024)
To improve the homogeneity of heating, the magnetic absorbing material Fe3O4 is considered to use in microwave pyrolysis of oily sludge. Therefore, the effect of Fe3O4 on the microwave pyrolysis of oily sludge is investigated based on gas volatile products. Thermogravimetric mass spectrometry result certifies that Fe3O4 will increase the weight-loss ratio from 13.0% to 14.1%. Also, the characteristic peak intensity of CO in gas products decreases from 5.41 × 10-10 A/g to 1.95 × 10-10 A/g, while H2O increases from 3.57 × 10-10 A/g to 7.32 × 10-10 A/g and CO2 increases from 6.87 × 10-10 A/g to 8.92 × 10-10 A/g. This is caused by the esterification of alcohols and esters and the reduction of Fe3O4 by CO. Based on the decrease in activation energy and enthalpy values of Stage II and IV, it infers that Fe3O4 catalyzes the pyrolysis process of oily sludge to some extent. Similarly, gas chromatography-mass spectrometry results show that Fe3O4 can make the types of gas products increase. Especially, the number of molecular species increases from 5 to 46 under 200-300 °C. Finally, a simple molecular dynamics simulation model is conducted, and the results are in agreement with the experimental results. This study shows that Fe3O4 improves the pyrolysis homogeneity and the pyrolysis efficiency also improves